Streetscape Enhancement for Supporting City Tourism Development - B. Saroinsong, Fabiola; H. E. Sendouw, Recky (International Journal of Psychosocial Rehabilitation, 2020)
Cities all over the world are facing strong competition in terms of attracting tourists. In tourism specifically, the competitive advantage is determined by services orientation and tourism characteristics of the city. The image of a city and tourist’s real experience directly impacts tourist satisfaction and selling points for the city. Streetscape design plays an important role in affecting the perception and experience of a city. This article reviews the streetscape enhancement for maintaining and improving Tomohon City’s physical and visual aspects that support tourism development. The community and environmental context, elements and conditions which are investigated and analyzed include 3 main categories: 1. Ecological conditions: natural values, topography, climatic conditions, waste disposal. 2. Community and socio-economic conditions: resources, activity types, community’s craftsmanship, traditions, informal vendors. 3. Cultural values, infrastructure, and architectural conditions: urban form, architectural details, visual identity (city visual image), road, pedestrian path and bridge condition, land use, materials, streetscape elements, land values, infrastructure. There are five zones of the streetscape, which are gateway, agricultural land, rest area, residential neighborhood, and commercial corridors and public service area. Some designs of streetscape elements are proposed with concern about maintaining a high-quality built environment, building city identity, highlighting good views, and connecting people to amenities and services.